Analisis Efisiensi Kinerja Jaringan 4g LTE pada Aplikasi Video Conference - Dwi Pratiwi; Kms Andi (Penerbit Goodwood, 2024)
Purpose: Video conference is one of the multimedia services that is done in real time and allows for voice, image and data communication. constrained by network connection which causes the ongoing video conference process to be disrupted. These disturbances include unstable internet connection, low bandwidth, joining meeting time out and cannot connect to internet services. The need for fast internet access with the best performance in providing user comfort when conducting video conferences. Method: The system development methodology that will be used in this research process uses the AR (Action Research) method. Result: The focus of this study is to measure the performance of the 4G LTE network so that the video conference process can run smoothly using QoS parameters. There are two QoS methods used including Intrinsic QoS obtained based on data measurement parameters consisting of packet loss, throughput, delay and jitter. Perceived QoS is obtained when the service is used using the MOS (Mean Opinion Score) method consisting of MOS E-Model and MPQM. The two protocols that are filtered include the TCP and UDP protocols. This measurement aims to provide an assessment of LTE network performance when conducting video conferences in order to meet the ITU-T and TIPHON standard criteria in providing comfort to users when communicating using an ISP (Internet Service Provider)